Folktales aloud : practical advice for playful storytelling - Del Negro, Janice (ALA editions, An imprint of the American Library Association, 2014)
Storytelling in the library and school setting can take many forms. Del Negro encourages you to explore the folktales on your shelves and tailor them for the various age groups, involving the children in the storytelling as a way to learn through play, and letting them express the tales in their own words and ways.